Soaring of the Gulf Falcons : Diversification in the GCC Oil Exporters in Seven Propositions - Cherif, Reda.; Hasanov, Fuad. (Washington, D.C. : International Monetary Fund, 2014)
A key priority for the Gulf Cooperation Council (GCC) countries is to create a dynamic non-oil tradable sector to support sustainable growth. Since export diversification takes a long time, it has to start now. We argue that the failure to diversify away from oil stems mainly from market failures rather than government failures. To tackle market failures, the government needs to change the incentive structure for workers and firms. Experiences of oil exporters that managed to diversify suggest that a focus on competing in international markets and an emphasis on technological upgrade and climbing the 'quality ladder' are crucial.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet